More Synergy with Less Energy : A Partnership Approach to Achieving Results in Financial Infrastructure - Rafi, Taha; Maddedu, Oscar (World Bank, Washington, DC, 2012)
How do you achieve advisory services results on a shoestring budget and two staff? The many variables involved in managing and growing any regional program, including significant time spent in procuring expertise and short-term consultants, and in fund-raising to reduce the time available for project delivery. These necessary distractions shift the focus away from managing client relationships and achieving impact. And, at times, they can affect the quality of outputs. This smart lesson talks about using strategic partnerships to help balance the external and internal factors while expanding outreach and remaining responsive to clients. With this approach our team has gone from 'how do we make it through this financial year without a drop in client satisfaction and low supervision results' to 'our clients are so pleased that they're talking with International Finance Corporation (IFC) CEO Lars Thunell about expanding their IFC relationship!'